Technological schemes for deferrization of groundwater in the Tyumen region - A. G. Zhulin; O. V. Sidorenko; L. V. Belova (Архитектура, строительство, транспорт)
Since the late 1970s, groundwater in the Tyumen region was widely used for drinking water supply. It was the reason of the widespread construction of deferrization stations. Analysis of literature and monitoring of some deferrization stations in the region for a long time allowed us to systematise the applied deferrization technologies in chronological order as they become more complex. The method of deferrization with simplified aeration was the most widespread in the initial stages. This decision facilitated the introduction of block-complete deferrization stations at medium and small capacity facilities. Nowadays, there is a transition from reagentless methods to reagent methods due to tightening of requirements to drinking water quality. This, accordingly, leads to the rejection of typical technological schemes of deferrization and the use of water treatment plants assembled from standard equipment units.The review of foreign and domestic studies showed that the existing results of their generalisation in the form of some mathematical dependencies were insufficient and required further study and additional research. The technologies offered today are more complex but they are not economically optimal and efficient.